Corruption and growth in Sub Saharan African countries: Do differences in government effectiveness matter? - Gebresilassie, Yibrah Hagos; Gebrihet, Hafte Gebreselassie; Woldu, Gabriel Temesgen (Journal of Social Economics Research, 2024)
Corruption remains a significant global concern and affects economic growth ( ). Despite extensive research on the relationship between corruption and economic growth in developed countries, the effects of corruption and governance on economic growth in countries in Sub-Saharan Africa (SSA) remain unclear. This study aims to fill this gap in the literature by examining the impacts of corruption, government effectiveness ( ), and their joint interactive effects on economic growth in a panel of 37 countries in SSA from 2012 to 2022. The data were from multiple sources (the World Bank, the International Monetary Fund, and Transparency International) and analyzed using a two‑step generalized method of moments (SGMM) technique. The results of the SGMM demonstrate that corruption has a detrimental effect on the economic growth of countries in the SSA. Furthermore, the findings of the analysis reveal that government effectiveness significantly lowers the economic growth of countries in Sub-Saharan Africa. Most importantly, the results of regression analysis indicate that the joint interactive effect of corruption and government effectiveness ( ) depresses economies in countries in Sub-Saharan Africa, which is a novel finding. Therefore, this study recommends that in order to support the long-term economic growth of Sub-Saharan African nations, governments should create policies and strategies to combat corruption and improve institutional quality.